Jornalismo e mobilidade: características do app do Jornal Folha de S. Paulo - Souza, Sarah Melisa Barros de (Universidade Federal do Tocantins, 2020)
The objective of this paper is to analyze the application of the newspaper Folha de S. Paulo in relation to its structure, describing its particularities based on the precepts of mobile journalism and observing the way Folha de S. Paulo has behaved in the face of new technologies. In addition, it also seeks to present the possibilities of journalism focused on mobile media in Brazil. Regarding the methodology, this research fits in the deductive method. It is also basic in nature and qualitative in approach. Besides being exploratory and using the case study method. Among the procedures adopted are the bibliographic survey, the application description, information collection, material analysis and interpretation of results. At the end of the analysis it was possible to verify that the Folha de S. Paulo application partially fits the characteristics of mobile journalism, since even if it meets most of the elements, it does not fully perform its functionality.